SUMBER DAYA MANUSIA BERKARAKTER: ELIGIBLE DI ERA MEA (MASYARAKAT EKONOMI ASEAN) - Nur Hamidi (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2015)
Human resources is the ability of individuals both mind and physical power of a person in achieving the goals effectively and efficiently. Human resources in one country is different with other countries. Human resources is the one used by countries to develop their respective countries into a better country in all fields. In the era of the ASEAN economic community, eligible human resources urgently needed by a country so that the country can integrate with other countries. Developed countries will easily adapt to the era of the ASEAN economic community, but in contrary, countries that do not have high human resources have to prepare the human resources to be available in the era of the ASEAN economic community in the late 2015’s. The following strategies can be used to prepare eligible human resources in an ASEAN Economic Community era. They are: (1) Provide special skills possessed by a certain region that is different from other regions; (2) Embedding strong and visionary souls in competing with other countries; (3) Having high attitude towards serving customers. This can be evidenced by language and tools/technology mastery according to the specifications of the individual.